Improving the Quality of Education Management Through Strategic Planning and Leadership of School Principals in the Papua Region - Baharuddin; Muhammad Resky; Lusiana (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The swift advancement of worldwide education necessitates the enhancement of Education Management quality to guarantee educational standards, particularly in Papua, which faces geographical obstacles and infrastructural limitations. This service seeks to enhance the quality of Education Management in Papua by fortifying the leadership of school principals and executing strategic planning tailored to local conditions. Papua confronts significant obstacles in education, including inadequate infrastructure and accessibility, although the existing special autonomy legislation. This program, conducted from November 4-7, 2024, in Jayapura, engaged administrators, teachers, and educational staff in an interactive training encompassing theory, discussion, practice, and mentoring. Effectively enhance participants' knowledge and skills in formulating school strategic planning, while also inspiring them to execute the strategy. Participants expressed considerable satisfaction with the materials and methodologies employed; nevertheless, suggestions were made to extend the time of the question-and-answer session and enhance the utilisation of technology in the training process. The significance of this service indicates that enhancing educational quality in Papua is largely contingent upon fortifying the role of school principals as strategic leaders. By use of organised training and mentorship, school principals can more efficiently formulate and execute strategic planning that addresses local need.